BIOMATRICONDITIONING BENIH DENGAN RIZOBAKTERI UNTUK MENINGKATKAN PERTUMBUHAN DAN HASIL TANAMAN SORGUM (SORGHUM BICOLOR L.) - Handayani, Fitrianti; Sutariati, Gusti Ayu Kade; Madiki, Abdul (Universitas Medan Area, 2019)
The experiment was aimed to know the effect of seed biomatriconditioning with rhizobacteria to improve growth and yield of sorghum (Sorghum bicolor L.). The experiment was conducted in the Field of Animal Husbandry Agriculture Faculty, Haluoleo University from August up to November 2010. The experiment was arranged based on randomized completely design (CRD) which consisted of 5 seed biomatriconditioning with rhizobacteria treatments, namely: without seed biomatriconditioning (M0), seed biomatriconditioning with Bacillus sp. CKD061 + rice hulls charcoal (M1), seed biomatriconditioning with Bacillus sp. CKD061 + red brick powder (M2), seed biomatriconditioning with Pseudomonas fluorescens PG01 + rice hulls charcoal (M3), and seed biomatriconditioning with Pseudomonas fluorescens PG01 + red brick powder (M4). Every treatment was replicated 3 times, therefore, overall there were 15 experimental units. Data obtained were analized using analysis of variance and followed with Duncan?s Multiple Range Test. The result showed that seed treatment with biomatriconditioning using rhizobacteria gave significant effect in improving growth and yield of sorghum. Seed biomatriconditioning with sp. Bacillus CKD061 + red brick powder was the most effective treatment in increasing plant height, leaf area, dry weight of plant bomass, grain weight, and 1000 seed weight of sorghum.